2007
DOI: 10.1016/j.pain.2007.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Mental disorders among persons with chronic back or neck pain: Results from the world mental health surveys

Abstract: This paper reports cross-national data concerning back or neck pain comorbidity with mental disorders. We assessed (a) the prevalence of chronic back/neck pain, (b) the prevalence of mental disorders among people with chronic back/neck pain, (c) which mental disorder had strongest associations with chronic back/neck pain, and (d) whether these associations are consistent across countries. Population surveys of community-dwelling adults were carried out in 17 countries in Europe, the Americas, the Middle East, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
317
2
17

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 530 publications
(367 citation statements)
references
References 39 publications
31
317
2
17
Order By: Relevance
“…Fourth, the PSP category groupings were based on previous research 29,42,43 but could not account for potentially important differences within some categories (e.g., paramedics verses emergency medical technicians). Fifth, future research should simultaneously assess the interactive effects of mental health and chronic pain, given the substantial evidence of comorbidity [44][45][46][47] and potentially increased risk from mutually maintaining factors.…”
Section: Limitationsmentioning
confidence: 99%
“…Fourth, the PSP category groupings were based on previous research 29,42,43 but could not account for potentially important differences within some categories (e.g., paramedics verses emergency medical technicians). Fifth, future research should simultaneously assess the interactive effects of mental health and chronic pain, given the substantial evidence of comorbidity [44][45][46][47] and potentially increased risk from mutually maintaining factors.…”
Section: Limitationsmentioning
confidence: 99%
“…Such data would be valuable as depression is highly pervasive among people in LMICs (Andreasen et al, 2014, Guerra et al, 2016, Prina et al, 2011. To date, three large-scale studies have investigated pain and depression comorbidity across multiple countries including a small number of LMICs (Demyttenaere et al, 2007, Gureje et al, 2008, Tsang et al, 2008. These studies found that across 18 countries (8 in LMICs), people with multisite pain (Gureje et al, 2008) and chronic pain (Tsang et al, 2008) are at increased risk of mood disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Given the suggestion that the association between somatic symptoms, including pain conditions, and psychiatric illness may be influenced by cultural factors 8 however the generalizability of these findings to non-Western populations is an important question 9 . Recently, a worldwide study examining a population-based sample from 18 developed and developing countries, has carefully examined the relationship between chronic pain and mental disorders 9,10 .…”
Section: Introductionmentioning
confidence: 99%